Development of the student affairs officers work environment perception scale - Haynes, Derrick Eugene, author; Gilley, Jerry W., advisor; Makela, Carole J., committee member; Scott, Malcolm E., committee member; Venneberg, Donald L., committee member (Colorado State University. Libraries, 2010)
The qualitative and quantitative study developed and validated a questionnaire to measure Student Affairs Officers' (SAO) perceptions of the work environment. A review of the literature identified five major categories and 25 elements having an impact on SAOs' perceptions of the work environment. The test instrument (questionnaire) was developed through a focus group informed by the literature with Student Affairs Leaders (SAL). The process yielded a test instrument with 125 items. During February 2010, 1,723 SAOs who are members of Student Affairs Administrators in Higher Education (NASPA) were invited to respond to the Student Affairs Officers Work Environment Perception Scale (SAOWEPS) questionnaire. Of those invited, 702 SAOs responded, yielding a 41% response rate. SAOWEPS was administered online using SurveyMonkey. Exploratory factor analysis (EFA) was conducted to analyze data. EFA identified five factors (relationship between SAL/SAO, job design and ability to do the work, job engagement and satisfaction, workgroup effectiveness, and organizational climate and commitment). In addition, the items were reduced from 125 to 59. The Cronhach's alpha of .962 was found for the 59 items and these items account for 52.3% of the variance with five factors. Data from the validated questionnaire was analyzed to determine if differences between work environment perceptions exist for SAOs who have 1-4 years (n = 215) and 5 or more years of experience (n = 487). An independent samples t test was conducted with the two groups and no significance was found. The researcher then split the two groups into three groups (SAOs with 1-4 years of experience, n = 215 (M = 41.12, SD = 11.90), for SAOs with 5-10 years of experience, n = 322 (M = 43.33, SD = 12.30), and n = 165 (M = 42.55, SD = 12.40) for SAOs with 11+ years of experience) and conducted a one-way ANOVA to see if differences existed. However no significant differences were found. The outcome of the study developed and validated a questionnaire, which measures SAOs' perceptions of the work environment. The questionnaire is useful as it provides SALs with a way to assess a student affairs department or division. Ultimately, SAOWEPS provides insight into the work environment as perceived by SAOs.
Department Head: Carole J. Makela.
Keywords: work environment; t-test; student affairs; perception development; management; factor analysis; Student affairs administrators; Student affairs services -- Psychological aspects; Work environment -- Psychological aspects; Organizational behavior -- Research